PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN TANAMAN PAKAN LEBAH TRIGONA DI DUSUN BANGKO KABUPATEN HALMAHERA BARAT - Tamnge, Fadila; Nurdin, Aqshan Shadikin (Universitas Padjadjaran, 2026)
West Halmahera Regency holds significant potential for the development of its agricultural and livestock sectors, including the cultivation of forage plants for Trigona bees. Bangko Hamlet, located within this region, exhibits rich biodiversity that supports the domestication of Trigona spp., a genus of stingless bees renowned for producing high-quality honey. This community engagement program aimed to (1) enhance the availability of forage resources for Trigona bees through the management of flowering plants and (2) empower local partners to actively participate in sustainable land management practices. The program was implemented using the Participatory Rural Appraisal (PRA) approach, which emphasizes community involvement throughout all stages of the program. The introduction of nine flowering plant species in Bangko Hamlet successfully increased the sustainable supply of nectar and pollen for the colonies, leading to an approximate 50% increase in average honey production per colony. Furthermore, the establishment of two local management groups contributed to the development of small-scale enterprises centered on Trigona honey production. A locally branded product,